Preparation, characterization and photocatalytic properties of Ho doped ZnO nanostructures synthesized by sonochemical method - Anukorn Phuruangrat (2018)
The three-dimensional flowerlike undoped and Ho doped ZnO microstructure was successfully synthesized by a sonochemical method. The morphologies and structures of the phase were characterized by the analyses of XRD, SEM and TEM. The flower-like structure composed of numerous one-dimensional hexagonal nanoprisms ZnO and Ho doped ZnO were revealed as hexagonal crystal structure with exposure (0 0 1) facet. The Ho doped ZnO exhibited a relatively higher photocatalytic activity than the pure ZnO in the degradation of methylene blue under UV light. © 2013 Elsevier Ltd. All rights reserved.